Disability Justice and Libraries: An Indonesian Experience - Saputri, Atha Difa; Arifin, Ridwan (Brawijaya University Library, 2023)
This research explores the intersection of disability justice and library services in Indonesia. The study investigates the challenges faced by individuals with disabilities in accessing library resources and services and examines the initiatives taken by Indonesian libraries to promote inclusivity and equity. This research involves a qualitative analysis of the experiences of library users with disabilities, as well as interviews with library staff and administrators. It highlights the importance of designing libraries and services that accommodate diverse needs and abilities. The study also discusses the role of technology, adaptive equipment, and staff training in creating accessible library environments. The findings shed light on the progress made in advancing disability justice within the Indonesian library community and offer insights into the remaining barriers and opportunities for improvement. By sharing these experiences and strategies, this study contributes to the global discourse on disability justice and libraries, aiming to inspire positive change and greater inclusivity in library services worldwide.